The first case report of pediatric acute appendicitis caused by "Candidatus Actinobaculum timonae". Issue 3 (March 2022) - Iqbal, Asef; Fujimura, Takumi; Shinjoh, Masayoshi; Furuichi, Munehiro; Iimori, Takashi; Umeyama, Tomoshige; Ishida, Tsuyoshi; Morinaga, Shojiro; Kamimaki, Isamu; Ohkusu, Kiyofumi; Takahashi, Takao
Abstract: A 14-year-old boy presented to the hospital with pain in the right lower abdomen. His condition was diagnosed as acute appendicitis. An emergency operation was performed, and histopathological examination revealed an actinomycete-related organism in the excised appendicitis specimen. On 16S rRNA gene sequence analysis, " Candidatus Actinobaculum timonae" was identified, which is the first known case in a pediatric patient.